EDUCATIONAL GAME APPLICATION FOR LEARNING INTEGER OPERATION MATERIALS FOR ELEMENTARY SCHOOL STUDENTS BASED ON ANDROID - Trisnawati, Trisnawati; Ena Anjely, Putri Ayu (JECE (Journal of Ethics and Character Education), 2023)
Currently, elementary school students' enthusiasm for understanding integer material has diminished, as the teaching methods need to be more engaging and enjoyable. With this innovative breakthrough, it will facilitate teachers and students in understanding how the technical aspects of the teaching and learning process can be more effective and efficient. This innovation aims to make it easier for students to review and comprehend integer material anytime and anywhere. An educational game application for learning integer material will be developed, which can be installed on students' Android-based phones or smartphones. This way, students can easily access explanations of integer material. The school is actively embracing innovation in its teaching and learning processes. One of the innovations that will be implemented at Elementary School or students at State Elementary School 1 Yogyakarta Pringsewu is the introduction of an educational game application. This application will assist both teachers and students in quickly grasping the concepts of integer material.